Sila-Sila Pancasila Sebagai Landasan Etika dalam Kehidupan Mahasiswa dan Pekerja - Arteta , Naswa Ine; Nur Salsabila, Fatimah Az-Zahroh; Ramadhani Andrijanto, Keysha; Ika Puspita, Ari Mentalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article discusses the role of the Pancasila Principles as a foundation for ethics in the lives of students and workers in Indonesia. Pancasila, as the basis of the state, not only functions as a guideline for the nation and state, but also has strong relevance in shaping individual character and behavior. Through a qualitative approach, this research analyzes how each Pancasila principle can be applied in the context of the daily lives of students and workers, as well as its impact on professional and social ethics. The research results show that the application of Pancasila values, such as social justice, unity and humanity, is able to increase integrity, responsibility and solidarity among students and workers. Apart from that, this article also identifies the challenges faced in implementing these values ​​in the modern era, as well as providing recommendations for strengthening the understanding and practice of Pancasila in educational environments and the world of work. Thus, Pancasila is not only a symbol of national identity, but also a relevant ethical guideline in building a civilized society and with integrity.